DEMOCRATIZATION OF ACCESS TO JUSTICE: OBSTACLES AND PATHS TO THE ENFORCEMENT OF FUNDAMENTAL RIGHTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The article analyzes the right of access to justice as the basis of citizenship in the Democratic Rule of Law, highlighting its importance for the realization of fundamental rights. It addresses contemporary challenges, such as procedural slowness, high costs and the influence of the media on the public perception of Justice. It proposes the use of alternative conflict resolution mechanisms and the need for structural reforms to democratize access to justice and promote a more just and egalitarian society. The method used was deductive, based on data and literary review.Keywords: Citizenship. Access to justice. Fake news. Equality. Conflicts.